The doctor-patient argumentation: the problem of communication from a rhetorical and bioethical point of view - Caporale, Cinzia; Zagarella, Roberta Martina (Medicina e Morale, 2020)
In the era of medical post-paternalism, the doctor-patient communication has been investigated from many different perspectives. In general, however, these researches imply a view of language that is problematic both from a theoretical and bioethical point of view. Starting from this consideration, in the first part of the article we analyze the discursive doctor-patient interaction within the context of philosophy of language, discussing in particular three widespread and false beliefs about communication (language as a tool; the transmission model of communication; prejudice against persuasion). Cleared the field from these prejudices, in the second part two diverse models of argumentation are compared (pragma-dialectics and rhetoric), in favour of an intertwining between rhetoric and bioethics in describing the doctor-patient interaction.